2015
DOI: 10.3390/en8020859
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Water Gasification of Biomass: A Literature and Technology Overview

Abstract: Abstract:The supercritical water gasification process is an alternative to both conventional gasification as well as anaerobic digestion as it does not require drying and the process takes place at much shorter residence times; a few minutes at most. The drastic changes in the thermo-physical properties of water from the liquid state to the supercritical state make it a promising technology for the efficient conversion of wet biomass into a product gas that after upgrading can be used as substitute natural gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(109 citation statements)
references
References 144 publications
1
94
0
Order By: Relevance
“…states that in a laboratory environment, it is possible to pump wet biomass of up to 40 wt% dry matter content [13]. Stolten et al states that depending on the type of wet biomass, only biomass that has up to 20 wt% dry matter content is pumpable [33].…”
Section: Direct Injection System Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…states that in a laboratory environment, it is possible to pump wet biomass of up to 40 wt% dry matter content [13]. Stolten et al states that depending on the type of wet biomass, only biomass that has up to 20 wt% dry matter content is pumpable [33].…”
Section: Direct Injection System Limitationmentioning
confidence: 99%
“…In addition to this, the concept of SCWG utilization in a biorefinery is also gaining attention in recent years [12]. These recent developments, however, indicate the importance of overcoming a number of challenges [13]:…”
Section: Introductionmentioning
confidence: 99%
“…Also, catalytic activity, both homogenous and heterogeneous, has been investigated extensively with mixed reports [4]. In general what could be concluded that catalyst addition, especially alkali salts, could drive the process away from re-polymerization mechanisms and limit char formation [16]. However, it has been reported to increase gas and water-soluble organic fractions and present process upscaling challenges related to catalyst stability, poisoning and regeneration or recovery.…”
Section: Introductionmentioning
confidence: 99%
“…At such acute conditions, above the vapor pressure of water, the organic constituents of biomass are decomposed and valorized into a wider range of value added products. Extensive reviews on technology progress, the advantageous nature of supercritical water's chemical and physical properties and the up-to-date research findings can be found in the publications of Yakaboylo et al [4], Akiya et al [5], Kruse et al [6,7], Brunner [8], Loppinet-Serani et al [9], Knez et al [10], Peterson et al [11] and many others.…”
Section: Introductionmentioning
confidence: 99%
“…Yakaboylo et al [4] identified the varying properties of viscosity, density and dielectric constant of water around the critical point as the main reason behind it's suitability for biomass refining. Liquid water (at 25 • C and 1 bar), when upgraded into supercritical conditions, loses its characteristically polar tendency due to the destabilization of hydrogen bonds and, the acquirement of vapor-like density, density dependent di-electric constant and ionic product k w properties [4,5].…”
Section: Introductionmentioning
confidence: 99%